2018
DOI: 10.2139/ssrn.2847121
|View full text |Cite
|
Sign up to set email alerts
|

A Path Out: Prescription Drug Abuse, Treatment, and Suicide

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Another possibility is that a "must access" PDMP reduces the rate at which individuals become opioid misusers, delaying the effects on poisonings beyond our sample period. Borgschulte et al (2016) suggest that the impact of opioid control policies interacts with a state's capacity to provide substance abuse treatment to those who are now incentivized to reduce utilization. Your report results are displayed similar to the following: Note: Your search criteria and the recipient names you selected are located above your report.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that a "must access" PDMP reduces the rate at which individuals become opioid misusers, delaying the effects on poisonings beyond our sample period. Borgschulte et al (2016) suggest that the impact of opioid control policies interacts with a state's capacity to provide substance abuse treatment to those who are now incentivized to reduce utilization. Your report results are displayed similar to the following: Note: Your search criteria and the recipient names you selected are located above your report.…”
Section: Resultsmentioning
confidence: 99%
“…6 What remains unclear are the potential spillovers from these interventions, and any resulting success in reducing Rx drug misuse, on other outcomes. Opioid misuse has been linked with many adverse consequences including: higher health care costs (White et al 2005), lower worker productivity (Hansen et al 2011), more suicides (Borgschulte et al, 2018), and a complementary increase in cocaine and marijuana use (Grecu, Dave and Saffer 2019). Given the links between drug misuse, mental health, and crime, policies that lead to changes in Rx opioid abuse may also generate spillover effects on criminal behaviors, which could have substantial economic effects.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers found evidence that nonmandated PDMPs reduce fatal nonoxycodone-related overdoses and poisonings (Mallatt, 2017;Patrick et al, 2016;Simoni-Wastila and Qian, 2012), most of them found evidence of small or null effects on drug abuse (Simoni-Wastila and Qian, 2012; Meara et al, 2016). However, recent studies focusing on the effects of mandated PDMPs found significant effects on opioid quantity and shopping behavior, abuse outcomes, substance abuse facility admissions, crime rates, and fatal drug overdoses (Buchmueller and Carey, 2018;Patrick et al, 2016;Dave et al, 2017;Borgschulte et al, forth. ;Mallatt, 2017).…”
Section: Introductionmentioning
confidence: 99%